Моделювання статистичної характеристики робочої поверхні шліфувальних кругів - Шахбазов, Я. О.; Широков, В. В.; Грінер, І. М.; Сторощук, В. А. (Видавництво Львівської політехніки, 2017)
Проведено аналіз процесу шліфування та визначено шляхи технологічного забезпечення шорсткості обробленої поверхні цим методом; на підставі проведених теоретичних досліджень процесу здійснено правки шліфувальних кругів алмазними інструментами. Запропоновано модель статистичної характеристики робочої поверхні шліфувальних кругів після їх правки методом точіння алмазними інструментами.

Most grinding operations involves preliminary machining of abrasive discs work surface to create some relief and cutting properties depending on the requirements of the grinding process and the quality of the machined surface. Usually grinding in the self-sharpen mode is not ensured stability of the relief work surface, making it difficult to achieve the required surface roughness on the operations of details finishing treatment. The purpose of these studies is determining ways of predicting the effects of editing grinding wheels for technological support of surface roughness during grinding through the creation of model of the statistical characteristics of the working surface grinding wheels after revision by turning diamond tools. Calculations have shown that diamond grinding wheel editing can be performed with greater depth due to decreasing of radius at the top crystal. This can increase the stability of the abrasive wheel and reduce the number of amendments, which reduces the cost of grinding wheels during grinding. Thus, the results of calculations of the statistical characteristics of the working surface of the grinding wheel can be used to determine the technological conditions of grinding wheels corrections to ensure the roughness of surface and reduce costs across grinding operations. Developed and justified the use of model of the statistical characteristics of the working surface grinding wheels after revision by turning diamond tools for calculating the distance between the abrasive grains and kinematic component of surface roughness. According to the adopted law distribution and the calculation method inefficient spending of grinding wheel during editing process at 30 - 50% preservation of grains on the working surface can be reduced within 10... 20 % by selecting the diamond crystal size of ruling tool.
Modeling statistical data labor surface grinding wheels
Keywords: шліфувальний круг; алмазний інструмент; правка; рельєф; абразивне зерно; grinding wheels; diamond tools; editing; relief; abrasive grain; 621.91